Postklasična teorija pripovedi - Zupan Sosič, Alojzija (Slavistična revija, 2013)
"Postclassical narratology" is the term for narratology of the last three decades. However, the name is suitable only for the nontraditional theory of narrative that shifted its research focus from prose to narrative through the polyvalent theory of narrative. Connecting various academic disciplines is the main reason for the flourishing of narratology in the 21st century, while various currents, methods, and directions divided narratology into classical and postclassical narratology at the turn of the 20th century. The most important representatives of postclassical narratology are: cultural, cognitive, rhetorical, and feminist narratology, and the narratology of genderidentity.
Keywords: literarna teorija; literary theory; naratologija; narratology; narratorlogy; teorija pripovedi; theory of literature; theory of narrative